A double closed loop control algorithm based on current mode in full bridge circuit. Issue 1 (July 2021) - Xu, Chengbo; Chen, Jing; Li, Zhihua; Xiao, Chun
Abstract: In order to improve the problems of large output current and voltage ripples and slow system response when the full-bridge circuit is working. This paper proposes a double closed-loop control algorithm based on current mode. Use fuzzy controller to optimize the parameters of voltage outer loop PID controller. The genetic controller is used to optimize the parameters of the current inner loop PID controller. After the dual closed-loop structure of the current control mode is optimized for the traditional PID controller, the overshoot is reduced, the system response speed is accelerated and the current ripple and voltage ripple are also greatly reduced. The simulation verifies the effectiveness of the designed double closed-loop control algorithm.